Pemberdayaan Perempuan Untuk Meningkatkan Kualitas SDM Hospitaliti untuk Pariwisata Berkelanjutan : Studi Kasus Kota Tomohon, Sulawesi Utara - Rumadana, I Made; Kalpikawati, Ida Ayu; Kartini, Luh Putu; Winata, Adi Sistha; Kristiana, Nina Indra; Pitanatri, Putu Diah Sastri; Priliani, Ni Luh Dita (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This study examines the impact of intensive training on women's empowerment in Tomohon City, North Sulawesi, to support sustainable tourism by enhancing the quality of human resources in the hospitality sector. A total of 108 participants attended training sessions on entrepreneurship, accommodation management, and food presentation techniques. Data were collected using questionnaires and semi-structured interviews and analyzed through a mixed-method approach using SPSS version 25. The findings revealed significant improvements in technical skills (average score: 3.94, 98.61%), digital technology usage (average score: 3.94, 98.38%), business income (average score: 3.90, 97.45%), economic independence (average score: 3.92, 97.92%), and overall satisfaction with the training (average score: 3.95, 98.84%). Participants also reported increased confidence in managing their businesses and mastery of new techniques directly applied to their ventures. This research contributes significantly to the literature on women's empowerment through hospitality-based training to support sustainable tourism.